Neuroendocrine Regulation of Reproductive Dormancy in the Fruit Fly Drosophila melanogaster: A Review of Juvenile Hormone-Dependent Regulation - Kurogi, Yoshitomo; Mizuno, Yosuke; Imura, Eisuke; Niwa, Ryusuke (Frontiers in Ecology and Evolution, 2021)
Animals can adjust their physiology, helping them survive and reproduce under a wide range of environmental conditions. One of the strategies to endure unfavorable environmental conditions such as low temperature and limited food supplies is dormancy. In some insect species, this may manifest as reproductive dormancy, which causes their reproductive organs to be severely depleted under conditions unsuitable for reproduction. Reproductive dormancy in insects is induced by a reduction in juvenile hormones synthesized in the corpus allatum (pl. corpora allata; CA) in response to winter-specific environmental cues, such as low temperatures and short-day length. In recent years, significant progress has been made in the study of dormancy-inducing conditions dependent on CA control mechanisms in Drosophila melanogaster. This review summarizes dormancy control mechanisms in D. melanogaster and discusses the implications for future studies of insect dormancy, particularly focusing on juvenile hormone-dependent regulation.